Almost Hollywood, Nearly New Orleans The Lure of the Local Film Economy - Mayer, Vicki (University of California Press, 2017)
Early in the twenty-first century, Louisiana, one of the poorest states in the United States, redirected millions in tax dollars from the public coffers in an effort to become the top location site globally for the production of Hollywood films and television series. Why would lawmakers support such a policy? Why would citizens accept the policy's uncomfortable effects on their economy and culture? Almost Hollywood, Nearly New Orleans addresses these questions through a study of the local and everyday experiences of the film economy in New Orleans, Louisiana-a city that has twice taken the mantle of becoming a movie production capital. From the silent era to today's Hollywood South, Vicki Mayer explains that the aura of a film economy is inseparable from a prevailing sense of home, even as it changes that place irrevocably. "A scathing critique of the economic realities and broken promises of Hollywood South, told in rich ethnographic detail and passionately argued through Vicki Mayer's deep connection to New Orleans. This is a vital book." -NITIN GOVIL, author of Orienting Hollywood: A Century of Film Culture between Los Angeles and Bombay "Mayer guides readers through the numbers and arguments behind Louisiana's costly love affair with the film industry and raises important questions over whether the state's citizens are getting their money's worth." -STEPHANIE GRACE, columnist, The New Orleans Advocate "A visionary in the study of cultural labor, economy, and geography, Mayer is that rare writer who combines exquisite storytelling with rigorous scholarship. This is an essential contribution to film and media studies, and an urgent history lesson for policy makers." -MELISSA GREGG, author of Work's Intimacy VICKI MAYER is Professor of Communication at Tulane University. She is coeditor of the journal Television & New Media and author or editor of several books and journal articles about media production, creative industries, and cultural work.